2021
DOI: 10.3390/life11111178
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity of Medicinal Plant Extracts against Some Bacterial Pathogens Isolated from Raw and Processed Meat

Abstract: Background and aim: The poultry meat and its products are considered ideal media for bacterial growth and spoilage, as they are highly nutritive with a favorable pH. The food industry has focused its attention on a great diversity of plant species as food preservatives. The aim of this study was to investigate the presence of Staphylococcus aureus, Escherichia coli O157: H7, and Klebsiella pneumonia in food samples and to evaluate of the antibacterial activity of some medicinal plant extracts against these bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Anti-bacterial activity was determined via agar well diffusion [46,47]. Plant extract stock (10 mg/mL) was used in the concentration range of 6-10 mg/mL against microbial pathogens.…”
Section: Anti-bacterial Activitymentioning
confidence: 99%
“…Anti-bacterial activity was determined via agar well diffusion [46,47]. Plant extract stock (10 mg/mL) was used in the concentration range of 6-10 mg/mL against microbial pathogens.…”
Section: Anti-bacterial Activitymentioning
confidence: 99%
“…This result is not the same as the results of (Al-Deen 2017), who reported no inhibitory effect of Annona alcoholic seed extract against any of the pathogens Staphylococcus aureus, Klebsiella pneuomoniae and Escherichia coli using the agar diffusion technique. The agar diffusion method is widely used to evaluate the antimicrobial activity of plants or microbial extracts (Meshaal et al 2021).…”
Section: Agar Well Diffusion Techniquementioning
confidence: 99%
“…Recently, Zhang et al study showed that TGF-β is linked with the development of AIS severity, and a high TGF-β serum level can be used as an early diagnostic and prognostic biomarker [ 131 ]. In addition, SARS-CoV-2 infection may induce the release of inactive TGF-β in the lung, and latent TGF-β in the plasma, due to potent inflammatory and immune reactions with dysregulation of coagulations [ 132 , 133 ]. In severe COVID-19 with massive neutrophil infiltration in the lung, neutrophil elastase induces the release of TGF-β, which also recruits neutrophils into the lungs to create a positive-feedback loop in the activation and release of TGF-β [ 132 ].…”
Section: Role Of Neuropilin-1 In Covid-19mentioning
confidence: 99%